Significantly increased anti‐tumor activity of carcinoembryonic antigen‐specific chimeric antigen receptor T cells in combination with recombinant human IL‐12 - Xiaowei Chi; Peiwei Yang; Erhao Zhang; Jieyi Gu; Hui Xu; Mengwei Li; Xinmei Gao; Xin Li; Yinan Zhang; Hanmei Xu; Jialiang Hu (Cancer Medicine, 2019)
Abstract Background aims Chimeric antigen receptor T cells (CAR‐T cells) have been successfully used in treatments of hematological tumors, however, their anti‐tumor activity in solid tumor treatments was limited. As IL‐12 increases T‐cell immune functions, we designed carcinoembryonic antigen (CEA) specific CAR‐T (CEA‐CAR‐T) cells and, for the first time, used them in combination with recombinant human IL‐12 (rhIL‐12) to treat several types of solid tumors. Methods In vitro anti‐tumor activity of CEA‐CAR‐T cells in combination with rhIL‐12 was confirmed by evaluation of CEA‐CAR‐T cell activation, proliferation, and cytotoxicity after co‐incubation with CEA‐positive or CEA‐negative human tumor cells. In vivo anti‐tumor activity of CEA‐CAR‐T cells in combination with rhIL‐12 was confirmed in a xenograft model in nude mice for treatments of several types of solid tumors. Results In vitro experiments confirmed that rhIL‐12 significantly increased the activation, proliferation, and cytotoxicity of CEA‐CAR‐T cells. Similarly, in vivo experiments found that CEA‐CAR‐T cells in combination with rhIL‐12 had significantly enhanced anti‐tumor activity than CEA‐CAR‐T cells in growth inhibition of newly colonized colorectal cancer cell HT‐29, pancreatic cancer cell AsPC‐1, and gastric cancer cell MGC803. Conclusions These works confirmed that simultaneous use of cytokines, for example, rhIL‐12, can increase the anti‐tumor activity of CAR‐T cells, especially for treatments of several types of solid tumors.